Bioactive nutraceuticals oligo-lactic acid and fermented soy extract alleviate cognitive decline in mice in part via anti-neuroinflammation and modulation of gut microbiota - Abdolmaleky, Hamid M.; Sheng, Yin; Zhou, Jin-Rong (Frontiers in Nutrition, 2023)
Cognition decline is associated with aging and certain diseases, such as neurodegenerative or neuropsychiatric disorders, diabetes and chronic kidney disease. Inflammation/ neuroinflammation is considered an important causal factor, and experimental evidence suggests that anti-inflammatory natural compounds may effectively prevent cognitive decline. The goal of this study was to evaluate the effects of two natural bioactive agents, oligo-lactic acid (LAP) and fermented soy extract (ImmunBalance, IMB), on cognition in an adenine-induced cognitive impairment mouse model and to investigate the modulation of related biomarkers. Male C57 black mice randomly assigned into the following experimental groups and received the corresponding treatment for two weeks before the use of adenine for model development: (1) negative control; (2) model control: injection of adenine at 50 mg/kg daily for 28 days; (3)-(4) IMB groups: adenine injection and IMB oral gavage at 250 and 1000 mg/kg BW, respectively; (5) LAP group: adenine injection and LAP oral gavage at 1000 mg/kg BW. After four weeks, Y maze and Barnes maze tests were used to evaluate mice cognitive performance. At the end of the experiment, brain tissues and cucum fecal samples were collected for analysis of gene expression and gut microbiota. Mice treated with LAP or IMB had significantly improved spatial working memory, spatial recognition memory (LAP only), novel object recognition, and spatial learning and memory, compared with those in the model group. Gene expression analysis showed that, among a panel of cognition related genes, six of them (ELOVL2, GLUT4, Nestein, SNCA, TGFB1, TGFB2) were significantly altered in the model group, and their expression levels were significantly reversed by LAP (SNCA, TGFB1) and/or IMB (ELOVL3, GLUT4, Nestin, TGFB1, TGFB2). On the other hand, the altered microbiome was attenuated only by IMB. In conclusion, our data demonstrated that LAP and IMB could improve cognitive performance in mice via distinct mechanisms of action. LAP may improve cognition in part via inhibiting neuroinflammation and energy metabolism, whereas IMB may improve cognition in part via inhibiting neuroinflammation, enhancing energy metabolism, increasing neurogenesis, and modulating gut microbiota.